The effect of wastewater disposal on the water quality and phytoplankton in Erbil wastewater channel. (Baghdad Science Journal, 2010)
In this study, phytoplankton density, chlorophyll-a, and selected physico- chemical parameters were investigated in Erbil wastewater channel. The surveys were carried out monthly from May 2003 to April 2004. Samplings were established on three sites from headwaters to the mouth. The results showed that pH was in alkaline side of neutrality, with significant differences (P